Comparison of the Bath Ankylosing Spondylitis Disease Activity Index and a modified version of the index in assessing disease activity in patients with ankylosing spondylitis without peripheral manifestations. Issue 11 (24th November 2008) - Song, I H; Rudwaleit, M; Listing, J; Sieper, J
Abstract : Objective: To compare the original Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) with a modified BASDAI without questions about peripheral arthritis (question 3) and enthesitis (question 4), here termed the mini-BASDAI, as an instrument to assess disease activity in patients with ankylosing spondylitis (AS) without peripheral manifestations. Methods: The mini-BASDAI was calculated by omitting questions 3 and 4. The correlation of the original BASDAI and the mini-BASDAI with patient global and other disease parameters was assessed in a total of 692 patients from three AS cohorts including one observational AS cohort and two clinical trial populations treated with non-steroidal anti-inflammatory drugs and tumour necrosis factor alpha inhibitors. Sensitivity to change was assessed by calculating effect sizes. Results: Up to 70% of AS patients did not have peripheral involvement. Patients with peripheral involvement had higher disease activity in all activity parameters. The mini-BASDAI had higher values compared with the original BASDAI, also in the subgroup with peripheral manifestations. However, the mini-BASDAI did not correlate better with other markers of disease activity compared with the original BASDAI. Furthermore, effect sizes of the original BASDAI and mini-BASDAI were comparable in the treatment trials. Interestingly, approximately 5% of active AS patients with pure axial disease manifestation were identified whose disease activity was underestimated by the original BASDAI. Conclusion: On a group level using the mini-BASDAI did not result in an advantage to assess disease activity or in the subgroup without peripheral involvement. In only approximately 5% of AS patients was the mini-BASDAI superior to the original BASDAI.